2018
DOI: 10.1007/s00253-018-9269-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of phage resistance in Staphylococcus aureus SA003 reveals different binding mechanisms for the closely related Twort-like phages ɸSA012 and ɸSA039

Abstract: We have previously generated strains of Staphylococcus aureus SA003 resistant to its specific phage ɸSA012 through a long-term coevolution experiment. However, the DNA mutations responsible for the phenotypic change of phage resistance are unknown. Whole-genome analysis revealed eight genes that acquired mutations: six point mutations (five missense mutations and one nonsense mutation) and two deletions. Complementation of the phage-resistant strains by the wild-type alleles showed that five genes were linked … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 76 publications
0
51
0
Order By: Relevance
“…ɸSA039 requires β-GlcNAc glycosylation of WTA by TarS (Azam et al 2018). In this study, we found that ɸSA039 could generate spontaneous mutants capable of infecting TarS-null S. aureus .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…ɸSA039 requires β-GlcNAc glycosylation of WTA by TarS (Azam et al 2018). In this study, we found that ɸSA039 could generate spontaneous mutants capable of infecting TarS-null S. aureus .…”
Section: Resultsmentioning
confidence: 99%
“…The gene was deleted by pCasSA plasmid with clustered regularly interspaced short palindromic repeats (CRISPR)-Cas9 system (Chen et al 2017). Plasmid construction was performed as previously described (Chen et al 2017; Azam et al 2018). Spacers were manually selected by searching the protospacer adjacent motif (PAM) region.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations